Open clusters: II fundamental parameters of B stars in Collinder 223, Hogg 16, NGC2645, NGC3114, and NGC6025 - Aidelman, Yael Judith (2015)
Context. The knowledge of accurate values of effective temperature, surface gravity, and luminosity of stars in open clusters is very important not only to derive cluster distances and ages but also to discuss the stellar structure and evolution. Unfortunately, stellar parameters are still very scarce. Aims. Our goal is to study five open clusters to derive stellar parameters of the B and Be star population and discuss the cluster properties. In a near future, we intend to gather a statistically relevant samples of Be stars to discuss their origin and evolution. Methods. We use the Barbier-Chalonge-Divan spectrophotometric system, based on the study of low-resolution spectra around the Balmer discontinuity, since it is independent of the interstellar and circumstellar extinction and provides accurate Hertzsprung-Russell diagrams and stellar parameters. Results. We determine stellar fundamental parameters, such as effective temperatures, surface gravities, spectral types, luminosity classes, absolute and bolometric magnitudes and colour gradient excesses of the stars in the field of Collinder 223, Hogg 16,NGC2645, NGC3114, and NGC6025. Additional information, mainly masses and ages of cluster stellar populations, is obtained using stellar evolution models. In most cases, stellar fundamental parameters have been derived for the first time. We also discuss the derived cluster properties of reddening, age and distance. Conclusions. Collinder 223 cluster parameters are E(B − V) = 0.25 ± 0.03 mag and (mv − Mv)0 = 11.21 ± 0.25 mag. In Hogg 16, we clearly distinguish two groups of stars (Hogg 16a and Hogg 16b) with very different mean true distance moduli (8.91 ± 0.26 mag and 12.51 ± 0.38 mag), mean colour excesses (0.26 ± 0.03 mag and 0.63 ± 0.08 mag), and spectral types (B early-type and B late-/Atype stars, respectively). The farthest group could be merged with Collinder 272. NGC2645 is a young cluster (<14 Myr) with E(B − V) = 0.58±0.05 mag and (mv − Mv)0 = 12.18±0.30 mag. The cluster parameters of NGC 3114 are E(B − V) = 0.10 ± 0.01 mag and (mv − Mv)0 = 9.20 ± 0.15 mag. This cluster presents an important population of Be star, but it is difficult to define the cluster membership of stars because of the high contamination by field stars or the possible overlapping with a nearby cluster. Finally, we derive the following cluster parameters of NGC6025: E(B − V) = 0.34 ± 0.02 mag, (mv − Mv)0 = 9.25 ± 0.17 mag, and an age between 40 Myr and 69 Myr. In all the cases, new Be candidate stars are reported based on the appearance of a second Balmer discontinuity.